Time dependency of thrombectomy for large artery atherosclerosis versus cardioembolic stroke subtypes: evidence from the ANGEL-ACT registry - Yue Yin; Hanlin Chen; Anxin Wang; Anxin Wang; Anxin Wang; Xiaoli Zhang; Xiaoli Zhang; Xiaoli Zhang; Miao Li; Ligang Song; Ligang Song; Ligang Song; et al. (Frontiers in Neurology)
IntroductionIn this study, we investigated the differences in clinical outcomes following endovascular thrombectomy among ischemic stroke subtypes caused by large artery atherosclerosis (LAA) versus cardioembolism (CE) and the time-dependent nature of these clinical outcomes based on the stroke subtypes. Methods: Study participants were selected from the Endovascular Treatment Key Technique and Emergency Workflow Improvement of Acute Ischemic Stroke Registry to conduct a post-hoc analysis of a prospective, observational study. We included 1,046 patients, who had either LAA or CE stroke subtypes based on the Trial of Org 10172 in Acute Stroke Treatment criteria, drawn from the thrombectomy cohort. The association between clinical outcomes and time from stroke onset-to-recanalization time (ORT) was analyzed using a logistic regression model.ResultsOverall, 545 (52.6%) and 491 (47.4%) patients were included in the LAA and CE groups, respectively. No significant difference was found in the 90-day clinical functional outcome between the LAA and CE patients when ORT was achieved within 240 min. Beyond 240 min, the rate of achieving a modified Rankin Scale score of 0–2 in patients with LAA was higher than that of patients with CE [48.17% versus 38.66%; odds ratio (OR) = 0.678, 95% confidence interval (CI) = 0.521–0.884, p = 0.0040], and after adjustment, the OR was 0.732 (95% CI: 0.537–0.998, p = 0.0486).ConclusionIn cases where the ORT exceeded 240 min, the clinical outcomes of patients with LAA were better than those of patients with CE, demonstrating a stronger time-dependency for achieving a favorable prognosis in patients with cardioembolic stroke.